Some Reflections on the Wider Significance of St Ephrem and the Syriac Tradition - P. Brock, Sebastian (Asian Horizons, 2008)
Vol. 2, No 2, December 2008. Pages 38-49 Some Reflections on the Wider Significance of St Ephrem and the Syriac Tradition Dr Sebastian P. Brock Dr Brock. in his article. conducts a journey to the rediscovery of the Syriac Orient and presents the importance of it for our times. According to the author. the Syriac Orient may appear from a purely worldly and material point of view to be just a poor relation of the Latin West and the Greek East. its spiritual and intellectual heritages are just as much to be valued as those of the Latin West and the Greek East. and so there is all the more reason to cherish it and share it. Dr Brock invites the scholars with sufficient knowledge of Syriac to draw on the abundance of riches that lie unexploited in the writings of the Syriac Fathers and to make these spiritual riches available through translations or adaptations into modern languages.